Forty Years of Theological Anthropology. Flick and Alszeghy, «Fondamenti» (1970) - Castro Pérez, Francisco A. (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
This year is the 40th anniversary of the publication of Fondamenti di una Antropologia Teologica (Firenze 1970), written by the Professors of the Gregorian University M. Flick and Z. Alszeghy. This article pays homage to the work that was intended as inauguration of a new theological treatise, the one we still call «Theological Anthropology» (although suggested by K. Rahner some years before). We consider some aspects that let us explain its importance and peculiarities. Firstly, Fondamenti is partially written in the theological atmosphere previous to Vatican Council II and appears in its wake. Secondly, the newness of the treatise matches with a newness of approach, connected with the anthropological turn of contemporary thought. Thirdly, already this first elaboration of a Theological Anthropology is mainly referred to Christ, the new man (Cf. GS 22). Finally, the historical-salvific and Christ-centered approach of the treatise concerns every single and concrete human being.
Keywords: theological method; reception; Second Vatican Council; christocentrism; history of salvation